Planet earth [ prepare to see it as never before - Fenton, George; Fothergill, Alastair; Weaver, Sigourney , 1949- (Discovery Commincations, 2007)
"Journey from the highest peaks to the deepest oceans--pole to pole across the Earth. State of the art filming techniques and dramatic Cineflex aerial photography give you a glimpse of the natural world that will astound your eyes for hours."--Container